Development proposals of national significance: The call-in power of the Resource Management Act - Taylor, Martyn (Victoria University of Wellington Law Review, 1995)
This article explores the legal nature of the "call-in" power of the Minister for the Environment ("the Minister") conferred by sections 140 to 149 of the Resource Management Act 1991 ("the RMA"). In particular, it compares the call-in with the conventional consent procedure and suggests methods for enhancing transparency and accountability. This article was written while awaiting the report of the Board of Inquiry into the Taranaki Combined Cycle proposal.